Beginning iPad application development - Lee, Wei-Meng (Wrox programmer to programmer, 2010)
"Learn to develop successful--and profitable--iPad applications. Eager to start developing applications for the iPad? Then look no further than the book in your hands. This comprehensive, hands-on approach to iPad development walks you through all the necessary tools and skills required for successful iPad app programming ... Explains the various types of iPad applications supported by the iPhone SDK; discusses the various types of screen orientations and ways to handle rotations ; covers the new gesture recognizers available in this release of the iPhone SDK; covers the new split view-based application project type -- Zeroes in on database storage using SQLite3; examines web services, bluetooth programming, and bonjour programming, covers Apple Push notification services programming."-- p. [4] of cover